2007
DOI: 10.1124/jpet.106.111344
|View full text |Cite
|
Sign up to set email alerts
|

(S)-1-((S)-2-{[1-(4-Amino-3-chloro-phenyl)-methanoyl]-amino}-3,3-dimethyl-butanoyl)-pyrrolidine-2-carboxylic acid ((2R,3S)-2-ethoxy-5-oxo-tetrahydro-furan-3-yl)-amide (VX-765), an Orally Available Selective Interleukin (IL)-Converting Enzyme/Caspase-1 Inhibitor, Exhibits Potent Anti-Inflammatory Activities by Inhibiting the Release of IL-1β and IL-18

Abstract: (S)-1-((S)-2-{[1-(4-Amino-3-chloro-phenyl)-methanoyl]-amino}-3,3-dimethyl-butanoyl)-pyrrolidine-2-carboxylic acid ((2R,3S)-2-ethoxy-5-oxo-tetrahydro-furan-3-yl)-amide (VX-765) is an orally absorbed prodrug of (S)-3-({1-[(S)-1-((S)-2-{[1-(4-amino-3-chlorophenyl)-methanoyl]-amino}-3,3-dimethyl-butanoyl)-pyrrolidin-2-yl]-methanoyl}-amino)-4-oxo-butyric acid (VRT-043198), a potent and selective inhibitor of interleukin-converting enzyme/ caspase-1 subfamily caspases. VRT-043198 exhibits 100-to 10,000-fold selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
185
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(194 citation statements)
references
References 41 publications
6
185
2
1
Order By: Relevance
“…Our observation that caspase-1-deficient mice are susceptible to CIA may appear as a contradiction to a previous report demonstrating that the chemical Casp1 inhibitor VX-765 provided protection against CIA (20). However, it should be noted that VX-765 is also an effective inhibitor of other inflammatory caspases.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our observation that caspase-1-deficient mice are susceptible to CIA may appear as a contradiction to a previous report demonstrating that the chemical Casp1 inhibitor VX-765 provided protection against CIA (20). However, it should be noted that VX-765 is also an effective inhibitor of other inflammatory caspases.…”
Section: Discussioncontrasting
confidence: 99%
“…The Induction of Humoral Immunity during Collagen-induced Arthritis Requires ASC, but Not Nlrp3 or Caspase-1-Both T cellmediated and humoral immune responses have been demonstrated to play an essential role in the pathogenesis of CIA (3)(4)20). To gain some insight into the mechanism by which ASC mediates CIA, we first determined the serum levels of CIIspecific antibodies in immunized mice at day 42 post-immunization.…”
Section: Asc Is Required For Collagen-induced Arthritis Independentlymentioning
confidence: 99%
“…Such difference was also found for IL-1β levels, as VX-765 only decreased IL-1β levels in the striatum but not in the cortex. VX-765 is an inhibitor of caspase-1, the primary cleaving and activating mechanism of IL-1β from its precursor, pro-IL-1β (17)(18)(19). These results further support the hypothesis that the effects of VX-765 in the brain are structure and region dependent.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, VX-765 could exert neuroprotective effects on MSA pathogenesis by reducing α-syn cleavage, hence limiting its toxicity and its ability to form aggregates. VX-765 is an orally active, well-tolerated, brain-penetrant prodrug that is hydrolyzed by esterases in vivo to produce a potent and selective caspase-1 inhibitor (17,18), an activity supported by the in vivo demonstration of reduced cleavage of pro-Interleukin-1β (IL-1β) to its activated form IL-1β, a proinflammatory process under control of caspase-1 (18)(19)(20).…”
mentioning
confidence: 99%
“…Detailed examinations of MS pathological specimens have demonstrated that oligodendrocyte injury and apoptosis can be accompanied by limited inflammation and may, in fact, represent the initial event of lesions formation (Lucchinetti et al, 2000;Barnett and Prineas, 2004). Therefore, exploring oligodendrocyte-related pathogenic mechanisms, in addition to the conventional immune-based ones, can be of independent therapeutic significance in MS. Perhaps targeting IRF-1 and Caspase 1 signaling by pharmaceutical agents can be of clinical utility in controlling the disease activity in MS (Lin and Hiscott, 1999;Wannamaker et al, 2007). Interferon-␤, a MS therapeutic and a strong inducer of IRF-1 expression, has been reported to exert a harmful effect on oligodendrocytes (Taniguchi et al, 2001;Heine et al, 2006;Trebst et al, 2007).…”
Section: Discussionmentioning
confidence: 99%